Genetically modified and unmodified cellular approaches to enhance graft versus leukemia effect, without increasing graft versus host disease: the use of allogeneic cytokine-induced killer cells - Rambaldi, Benedetta; Rizzuto, Giuliana; Rambaldi, Alessandro; Introna, Martino (Frontiers in Immunology, 2024)
Although allogeneic hematopoietic cell transplantation (HCT) represents a curative approach for many patients with hematological diseases, post-transplantation relapse occurs in 20-50% of cases, representing the primary cause of treatment failure and mortality. Alloreactive donor T cells are responsible for the graft versus leukemia (GvL) effect, which represents the key mechanism for the long-term curative effect of HCT. However, the downside is represented by graft versus host disease (GvHD), largely contributing to transplant-related mortality (TRM). Multiple factors play a role in regulating the delicate balance between GvL and GvHD, such as the optimization of the donor HLA and KIR match, the type of graft source, and the adaptive use of post-transplant cellular therapy.In addition to the standard donor lymphocyte infusion (DLI), several attempts were made to favor the GvL effect without increasing the GvHD risk. Selected DLI, NK DLI, activated DLI and more sophisticated genetically engineered cells can be employed. In this scenario, cytokine-induced killer (CIK) cells represent a suitable tool to boost GvL while minimizing GvHD. CIK cells are T lymphocytes activated in culture in the presence of monoclonal antibodies against CD3 (OKT3), interferon-gamma (IFN-g), and interleukin-2 (IL-2), characterized by the expression of markers typical of NK cells and T cells (CD3 + , CD56 + , with a prevalent CD8 + phenotype). CIK cells can mediate cytotoxicity through both MHC and non-MHC restricted recognition, which is the so-called "dual-functional capability" and display minimum alloreactivity. Allogeneic CIK cells showed a favorable rate of response, especially in the setting of minimal residual disease, with a rate of GvHD not exceeding 25%. Finally, the CIK cell platform can be adapted for chimeric antigen receptor (CAR) cell strategy, showing promising results in both preclinical and clinical settings. In this review, we describe the main immunological basis for the development of the GvL and the possible cellular therapy approaches used to boost it, with a particular focus on the use of CIK cells.